Control of lamination on bedding-parallel fractures in tight sandstone reservoirs: the seventh member of the upper Triassic Yanchang Formation in the Ordos Basin, China - Lu, Hao; Cao, Song; Dong, Shaoqun; Lyu, Wenya; Zeng, Lianbo (Frontiers in Earth Science, 2024)
The tight oil sandstone in the 7th member of the upper Triassic Yanchang Formation in the Ordos Basin, China, has low porosity and permeability. Bedding-parallel fractures play a crucial role in enhancing reservoir and flow capacity. Based on core and thin section data, most bedding-parallel fractures are unfilled, with apertures generally <40μm, mainly <10μm. Larger apertures correlate with smaller filling ratios. The distribution of BPFs is intricately governed by laminations' types, density, and thickness. (1) The degree of development of bedding-parallel fractures depends on the degree of difference in mechanical properties between adjacent laminations; (2) When the laminations density is within a range, as the laminations density increases, the bedding-parallel fractures also increase; When the density of the laminations continues to increase beyond this range, the degree of fracture of the bedding-parallel fractures decreases; (3) Bedding-parallel fractures in thick laminations mainly distribute along the edges, while in thin laminations, they mainly distribute in the middle. The change in the thickness of the laminations leads to a change in the development position of bedding-parallel fractures, indicating that the position of the plastic plane controls the development position of beddingparallel fractures; (4) When multiple laminations coexist, the type and thickness of the laminations jointly influence the development of bedding-parallel fractures. Plastic thin laminations are conducive to the development of bedding-parallel fractures, while brittle thick laminations are not conducive to the formation of bedding-parallel fractures. When the thickness of the plastic laminations is close to or less than that of the brittle laminations, the laminations type has a dominant influence on bedding-parallel fractures, conversely, the influence of laminations thickness on bedding-parallel fractures will be dominant.